Correlational Analysis Of Participation In The Al-Miftah Lil’ulum Co-Curricular Program And Intra-Curricular Arabic Achievement - Ahmad Munawar Rosyid; Pradibyo Herdiansyah (IJGIE (International Journal of Graduate of Islamic Education), 2026)
Intracurricular Arabic language learning in madrasas/pesantren often faces time constraints for rule reinforcement and intensive practice, necessitating a co-curricular program that can expand learning opportunities in a targeted manner. This study aims to analyze the relationship between student participation in the Al-Miftah Lil 'Ulum extracurricular activities which strengthens the foundations of nahwu–sharaf through structured materials (e.g., nadzam, color-coded tables, staged exercises) to accelerate morphological–syntactic analysis and text comprehension and academic achievement in the intrakurricular Arabic language. The research uses a quantitative approach with a correlational design. A sample of 32 students who actively participated in Al-Miftah Lil 'Ulum volume 2 and had Arabic language grade documents from the last semester was selected thru purposive sampling. Participation data was collected using a closed questionnaire with a 4-point Likert scale that had been expert-reviewed and item-validated, while achievement data was obtained thru report card documentation. Data analysis was conducted using descriptive statistics and the Spearman Rank correlation test at a significance level of 5%. The research results showed a very strong positive relationship between participation and achievement (ρ = 0.885; N = 32). The significance test for the correlation using the t-test yielded t_calculated = 10.42 (df = 30) and t_table = 2.042 (α = 0.05), thus t_calculated > t_table and the correlation was declared significant (p < 0.05). Thus, H0 is rejected and Ha is accepted, which means there is a significant relationship between Al-Miftah Lil 'Ulum extracurricular participation and intrakurricular Arabic achievement.